2021
DOI: 10.3390/economies9020064
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Economics of Conventional, Organic, and Alternative Agricultural Production Systems

Abstract: Agricultural production systems are a composite of philosophy, adoptability, and careful analysis of risks and rewards. The two dominant typologies include conventional and organics, while biotechnology (GM) and Integrated Pest Management (IPM) represent situational modifiers. We conducted a systematic review to weigh the economic merits—as well as intangibles through an economic lens—of each standalone system and system plus modifier, where applicable. Overall, 17,485 articles were found between ScienceDirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 61 publications
2
16
0
2
Order By: Relevance
“…Furthermore, the work of Ram and Jung (1991) states that such individuals who pursue product trial and repetitive use significantly reduce innovation resistance and allow for a positive post-adoption evaluation (satisfaction and attitude) within their group [48]. Organic farmers are aware that their yield is comparatively low compared to biotech farmers [49,50], and based on their narratives, they are interested in adopting biotech crops due to stable yields and resistance to pest and diseases. This was highlighted in testimonials by interviewed organic farmers such as by Respondent 38, who stated, "I want to test it.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the work of Ram and Jung (1991) states that such individuals who pursue product trial and repetitive use significantly reduce innovation resistance and allow for a positive post-adoption evaluation (satisfaction and attitude) within their group [48]. Organic farmers are aware that their yield is comparatively low compared to biotech farmers [49,50], and based on their narratives, they are interested in adopting biotech crops due to stable yields and resistance to pest and diseases. This was highlighted in testimonials by interviewed organic farmers such as by Respondent 38, who stated, "I want to test it.…”
Section: Discussionmentioning
confidence: 99%
“…We found that diversified systems promote more employment opportunities with no loss of profits when compared to simplified systems. The higher gross income and comparable profits in diversified systems in our study may be explained by higher productivity associated with increases in farm work and crop diversification (Branca et al, 2021;Durham and Mizik, 2021;Tey and Brindal, 2014). Improving data collection on labour inputs would help strengthen the evidence base.…”
Section: More Employment With No Loss Of Incomementioning
confidence: 68%
“…E gazdaságok azonban alacsonyabb hozamokkal szembesülnek, különösen a gyümölcs-, zöldség-és állattenyésztési ágazatokban. Ezzel együtt a biogazdálkodás jelentős helyi környezeti előnyökkel járhat (Durham & Mizik, 2021). Az 1. táblázat adatai mutatják, hogy az ökológiai termelés is árérzékeny és a filozófiát követő termelés mellett az eredményesség is kiemelten fontos, sőt valamikor fontosabb, mint az elvek.…”
Section: A Téma Tárgyalása/kutatási Eredményekunclassified